Noncovalent synthesis of supramolecular dendritic architectures in water - Broeren, Maarten A. C.; Linhardt, Jeffrey G.; Malda, Hinke; de Waal, Bas F. M.; Versteegen, Ron M.; Meijer, Joris T.; Löwik, Dennis W. P. M.; van Hest, Jan C. M.; van Genderen, Marcel H. P.; Meijer, E. W. (Journal of polymer science. Part A, Polymer chemistry, 2005)
Water‐soluble guest–host complexes are prepared in a two‐step process. For this a new, polydisperse ethylene glycol containing guest molecule is synthesized that is soluble in both chloroform and water. This guest is able to bind to urea–adamantyl‐modified poly(propylene imine) dendrimers in chloroform in a noncovalent manner. When the chloroform is slowly evaporated and D2O is added, the hydrophobic dendrimer is solubilized in water. This is not possible when the hydrophobic dendrimer is directly added to the hydrophilic guests in water. When the unmodified poly(ethylene glycol) starting material is used, no solubilization occurs, and this indicates that the urea–acetic acid head group is necessary to solubilize the dendrimer. Approximately 26 guests are required for solubilization of the dendrimer. A lower number of guests results in aggregation and precipitation of the dendrimer. A monodisperse guest molecule has been used in NMR studies to show that the guest molecule binds with its acidic head group to the periphery of the dendrimer. This methodology opens the way to functional dendrimer aggregates in aqueous media. © 2005 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 43: 6431–6437, 2005 A supramolecular synthesis is described to obtain stable dendritic aggregates in water. A poly(ethylene glycol) containing guest molecule is able to bind to urea–adamantyl‐modified poly(propylene imine) dendrimers in chloroform in a noncovalent manner, and can solubilize the hydrophobic dendrimer in water when chloroform is removed and D2O is added. This methodology opens the way to functional dendrimer aggregates in aqueous media.